Validation of the Opioid Overdose Risk Behavior Scale, version 2 (ORBS-2). (1st June 2021) - Elliott, Luther; Crasta, Dev; Khan, Maria; Roth, Alexis; Green, Traci; Kolodny, Andrew; Bennett, Alex S.
Highlights: The Overdose Risk Behavior Scale provides a comprehensive index of proximal opioid-related overdose risks. Factor analysis of the full scale identifies a 6-subscale division of the item into relatively independent groups of overdose risk behaviors. Five out of six subscales were positively associated with self-report of non-fatal opioid overdose experiences in longitudinal analysis. Experiences of Anxiety and Depression appear linked to polysubstance use patterns, particularly those involving opioids and benzodiazepines. Behaviors involving diverted (and potentially counterfeit) opioid pills were the strongest predictors of overdose experiences over time. Abstract: Objective: To examine the factor structure of a revised and expanded opioid overdose risk behavior scale and assess its associations with known overdose indicators and other clinical constructs. Background: Opioid-related overdose remains high in the U.S. We lack strong instrumentation for assessing behavioral risk factors. We revised and expanded the opioid overdose risk behavior scale (ORBS-1) for use among a broader range of people who use opioids. Setting & sampling frame: Using respondent-driven sampling we recruited adults (18+) reporting current unprescribed opioid use and New York City residence. Method: Participants (N = 575) completed the ORBS-1, ORBS-2, and a variety of clinical measures and then completed the ORBS-2 and overdose risk outcomes across monthly follow-up assessments over a 13-month period. Results: Principal components analysis was used to identify six ORBS-2 subscales, Prescription Opioid Misuse, Risky Non-Injection Use, Injection Drug Use, Concurrent Opioid and Benzodiazepine Use, Concurrent Opioid and Alcohol Use, and Multiple-Drug Polysubstance Use. All subscales showed moderate non-parametric correlations with the ORBS-1 and with corresponding clinical constructs. Five of the subscales were significantly ( p < .01) positively associated with self-reported non-fatal overdose. Of note, the Risky Non-Injection Use subscale was the most strongly associated with past-month overdose indicators. Conclusions: Psychometrics for the opioid overdose risk behavior subscales identified suggest the ongoing utility of risk behavioral instrumentation for epidemiological research and clinical practice focused on risk communication and minimization. Use of the entire ORBS-2 measure can provide insight into the proximal/behavioral factors of greatest concern to reduce overdose mortality.